Cardio Protective Effect of Neuregillin-1 against Cardio Toxicity Induced by Trastuzumab in Adult Mice - Yousuf Qays Majeed (Journal of Global Pharma Technology, 2018)
Objective: This work will be carried out to investigate the potential therapeutic effect of  Neuregulin-1 against cardio toxicity induced by trastuzumab in male mice Materials and Methods:  Forty five adult male and female mice (weighing 35-50 gm) were divided into 3 groups randomly, each group contains 15 animals, group A which received distilled water as control by using intraperitoneal injection (IP) route for 10 days group B, received Trastuzumab as 6 mg/kg/day by using intraperitoneal injection route for 10 days while group C, received Neuregulin-1 (2.5 mg/day/animal) just before the administration of Trastuzumab (6mg/kg/day) given by IP route for 10 days. The significance of difference was tested by using ANOVA followed by Tukey test. Statistical significance depends on the P<0.05. Results: Cardiac troponin I concentration was significantly elevated in the trastuzumab group when compared with the control group; while, concentration has been significantly lower in the group C when compared with the trastuzumab group. While, results of total antioxidant capacity had significantly higher in the group B and group C in compare with control group. Conclusion: Neuregulin-1 can be used as a cardio protective in cardiac complications of cancer treatment by its ability to attenuate the cardio toxic effect of trastuzumab by significantly lowering cardiac troponin I concentrations. Keywords: Neuregillin-1, Cardio toxicity, Trastuzumab, Cardiac troponins.